IJPS 2022
DOI: 10.36468/pharmaceutical-sciences.953
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial, Anticancer and Antidiabetic Potential of Freeze-dried Aqueous Borassus flabellifer L. Seed Powder Extract

Abstract: Banu et al.: Therapeutic analysis of Borassus flabellifer L. Seed PowderThe Borassus flabellifer fruit which is one of the summer fruits of India can be considered a promising therapeutic food as it is a good source of bioactive compounds. The aim of this study was to evaluate the antibacterial, anticancer and antidiabetic activity of the locally available aqueous freeze-dried seed powder extract of Borassus flabellifer. Antibacterial activity was evaluated using agar well diffusion assay against gram-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…An increase in absorbance correlates with the activity of the sample. 26,36,37 From this study, YLFF showed negative alpha-glucosidase inhibitory activity at sample concentrations ranging from 100 -2000 µg/mL. Meanwhile, according to data presented in Table 2, the OLFF sample showed very low alpha-glucosidase inhibitory activity with % inhibition on minimum test concentration of 100 µg/mL ranging from 0.3 -2.4 % and on maximum test concentration of 2000 µg/mL ranging from 8.6 -23%.…”
Section: Resultsmentioning
confidence: 61%
“…An increase in absorbance correlates with the activity of the sample. 26,36,37 From this study, YLFF showed negative alpha-glucosidase inhibitory activity at sample concentrations ranging from 100 -2000 µg/mL. Meanwhile, according to data presented in Table 2, the OLFF sample showed very low alpha-glucosidase inhibitory activity with % inhibition on minimum test concentration of 100 µg/mL ranging from 0.3 -2.4 % and on maximum test concentration of 2000 µg/mL ranging from 8.6 -23%.…”
Section: Resultsmentioning
confidence: 61%
“…abellifer seed powder as a prospective cure for a deadly illness. 9 When galactomannan was originally discovered in the so palm kernel, it was discovered to contain mannose (78.32%) and galactose (27.64-28.06%). Current research on the in vitro free radical scavenging potential of the carotenoids in palmyra fruit pulp revealed the types of free sugars and polysaccharides that are prevalent in the kernel.…”
Section: Introductionmentioning
confidence: 99%
“…The extract of B. flabellifer freeze-dried seed powder demonstrated maximal inhibition of Gram-negative bacteria ( E. coli and Klebsiella pneumoniae ), revealed acceptable anti-cancer, and demonstrated significant α-amylase and α-glucosidase inhibitory activity, confirming the utilization of B. flabellifer seed powder as a prospective cure for a deadly illness. 9 When galactomannan was originally discovered in the soft palm kernel, it was discovered to contain mannose (78.32%) and galactose (27.64–28.06%). Current research on the in vitro free radical scavenging potential of the carotenoids in palmyra fruit pulp revealed the types of free sugars and polysaccharides that are prevalent in the kernel.…”
Section: Introductionmentioning
confidence: 99%